Desempenho, medidas morfométricas IN VIVO e características da carcaça de cordeiros Santa Inês alimentados com resíduo de cervejaria desidratado - Araújo, Mayara Silva de (2016)
Was evaluated the effect of different levels of inclusion of brewers dried grains (BDG) on performance parameters, morphometric measurements in vivo and carcass characteristics of Santa Ines lambs. Thirty-five male lambs non-castrated with average initial weight of 16.00 ± kg, and, approximately, 70 days of age were used. Were adopted a completely randomized design with five treatments and seven replications, consisting the treatments to 0; 20; 40; 60 to 80% of inclusion of BDG in the concentrate portion of the ration. The duration of the experiment was determined by the time required for the mean body weight of animals of the treatment reached 28 kg, when the 35 animals were slaughtered. The final body weight decreased linearly with the addition of BDG (P<0.05). The average dry matter intake (g /day) differed between the rations (P<0.05). The body condition score decreased linearly (P>0.05) with the inclusion of the by-product. The different rations did not interfere with the body length and hind length values (P>0.05). The variables body weight, body weight at slaughter, hot carcass weight, cold carcass weight, hot and cold carcass yield and biological yield showed linear decrease linear effect (P<0.05), while for the variables empty body weight and loss of cooling, there was no effect (P>0.05). It was observed linear effect (P<0.05) for shoulder, rib and fore loin weights, expressed in kg, and for fore loin yield. There was a linear effect to the non-carcass components to respiratory system, liver, skin and feet weight, according to the increasing levels of BDG. Regarding carcass muscularity index, there was a decreasing linear effect (P<0.05) for the carcass compactness index (ICC). For the variables weight of the ham, subcutaneous fat, intramuscular fat, connective tissue, bone and muscle:fat ration, it was found a linear decrease (P<0.05). The increasing levels of brewers dried grains in Santa Ines lambs ration negatively influences the performance and carcass characteristics of animals, which can result in lower economic return on the commercialization of the meat from these animals.